Tindak Tutur Ekspresif Dalam Podcast Rukun Indonesia Tema Hidayah Sang Mualaf: Cewek Cantik Pembenci Islam Mualaf Dalam 7 Hari - Karly, Aisy; Asnawi, Asnawi (UIR Press, 2023)
This research is based on the scope of pragmatic studies, this research only focuses on expressive speech acts. What is the function of expressive speech acts in the Rukun Indonesia video podcast with the theme Hidayah the Convert: Beautiful Girl Who Hates Islam Converts to Islam in 7 Days? The aim of this research is to describe and analyze the function of expressive speech acts in the Rukun Indonesia podcast video with the theme Hidayah Sang Convert: Beautiful Girl Who Hates Islam Converts to Islam in 7 Days. The theory used in this research is Rahardi (2005:36). This research is included in qualitative research. From the results of processed data related to the Function of Expressive Speech Acts in the Rukun Indonesia Podcast Video, the theme Hidayah the Convert: Beautiful Girl Who Hates Islam Converts to Islam in 7 Days is dominated by speech acts expressing blame. In expressive speech acts of gratitude, it is known that there are three speech act data. In the expressive speech act of Blaming, there is one speech act data, namely 12 data. In the expressive speech act of Praising, there is one speech act data, namely 8 data. In the expressive speech act of condolence, it is known that it does not have any speech act aspects.